Fractional Integration via Picard Method for Solving Fractional Differential-Algebraic Systems - Susan H. Mohammad; Abdulghafor Mohammed Al-Rozbayani (Journal of Applied Mathematics)
In this paper, we applied an efficient integrative method called the fractional Picard method to find the approximate solution to a system of fractional algebraic differential equations (SFADEs). By comparing the results with the exact solution, it was found that this method is highly efficient for finding solutions. Also, a genetic algorithm (GA) was used to speed up the approximate solutions when choosing the best values for the fractional derivative, which increased the efficiency of Picard’s fractional integral method in finding the best solutions. The MATLAB program was used to find approximate solutions.